Ecological validity and deception detection research design. Issue 1 (2nd January 2018) - Levine, Timothy R
ABSTRACT: The concept of ecological validity is explicated and applied to deception detection research. The ecology of the deception lab typically involves researchers randomly assigning and instructing senders to lie or tell the truth. In lab-based lie detection tasks, receivers are prompted to make explicit truth-lie judgments in real time where truths and lies are equally probable, and where evidence and persuasion-based lie detection methods are precluded. Outside the lab, deceivers self-select, engage deception as a problem-solving activity, and have greater linguistic freedom to deceive in ways other than telling outright falsehoods. Receivers outside the lab face truth-lies base-rates other than 50–50, they are not prompted to consider the possibility of deception by a researcher, decisions about honesty often need not be immediate, and a wider variety of discovery methods are available. The implications of these differences are discussed in contexts of everyday conversation, criminal investigation, high stakes media lies, and security screenings.